Cancer Imprints an Increased PARP-1 and p53-Dependent Resistance to Oxidative Stress on Lymphocytes of Patients That Later Develop Alzheimer's Disease - Salech, Felipe; Ponce, Daniela P.; SanMartín, Carol D.; Rogers, Nicole K.; Henríquez, Mauricio; Behrens, Maria I. (Frontiers in Neuroscience, 2018)
We have proposed that a common biological mechanism deregulated in opposite directions might explain the inverse epidemiological association observed between Alzheimer’s disease (AD) and cancer. Accordingly, we showed that lymphocytes from AD patients have an increased susceptibility, whereas those from survivors of a skin cancer, an increased resistance to oxidative death induced by hydrogen peroxide (H2O2), compared to healthy controls (HC). We investigated the susceptibility to H2O2-induced death of lymphocytes in survivors of any type of cancer and in cancer survivors who later developed AD (Ca&AD). We also explored the involvement of Poly [ADP-ribose] polymerase-1 (PARP-1) and p53 pathways in the process, since both are involved in the increased death of AD lymphocytes. Lymphocytes from 11 cancer and 13 Ca&AD patients, and 12 HC were submitted to increasing concentrations of H2O2 for 20 hours. Cell death was determined by flow cytometry, in the presence or absence of PARP-1 inhibition (3-aminobenzamide, 3-ABA), or p53 inhibition (pifithrin-α) or stabilization (Nut-3). PARP-1 and p53 mRNA levels were determined by Real-Time PCR. Lymphocytes from cancer and Ca&AD patients showed increased survival compared to HC, without differences between them, opposite to the increased susceptibility to death previously shown in AD. PARP-1 inhibition provided marked protection from H2O2-induced death in the two group of patients, significantly greater than in HC. Pharmacological inhibition of p53 increased lymphocyte survival in Ca&AD patients, contrary to the effect previously reported in HC and AD. PARP-1 and p53 mRNA levels were elevated in Ca&AD lymphocytes compared with controls. In all, these results show that cancer imprints an increased resistance to H2O2-induced death in lymphocytes that persists after AD development, and is dependent on both PARP-1 and p53. p53 inhibition showed a differential role in cancer and Ca&AD compared to HC and AD lymphocytes, that could explain the inverse susceptibility to oxidative death in cancer and AD. These results are in agreement with the hypothesis of a common biological mechanism in AD and cancer. The similar cell death susceptibility and cell death pattern observed in cancer and Ca&AD lymphocytes suggests that cancer history leaves long term effects on lymphocyte cell death susceptibility.